Developing Early Childhood’s Character Through Javanese Traditional Game - Pranoto, Yuli Kurniawati Sugiyo; Sugiyo, Sugiyo; Hong, Jianzhong J (Indonesian Journal of Early Childhood Education Studies, 2014)
This research was intended to develop an innovative conceptual model for early childhood education programs to develop early childhood character through Javanese traditional game. The research employed a research and development approach. Two categories of the subject were used for this research; direct subjects, consist of 2-4-age; and indirect subjects consisting of teacher and materials. These subjects were taken by means of purposive random sampling. The needed data were collected by means of interviews and literature reading. The analyzes showed that subjects, both from student and teachers were highly enthusiastic playing those traditional games. These traditional games had simple rules, easy to apply especially for toddler. Besides, these traditional games had moral value to build toddler’s character.  This model has been effectively proven to build toddlers’ characters successfully. Teachers actively reviewed the learning outcomes of the children and gave useful inputs for further development for them. Generally speaking, it can be infered that by using this model has resulted on the improvement of toddlers’ characters which is indicated by self-quality. Therefore, it is recommended that the socializations of this model should not do by the school only, but also community members especially family.How to citePranoto, Y., Sugiyo, S., & Hong, J. (2014). Developing Early Childhood’s Character Through Javanese Traditional Game. Indonesian Journal Of Early Childhood Education Studies, 3(1), 54-58. doi:10.15294/ijeces.v3i1.9477